The Government Policy for the Ukraine’s Pharmaceutical Industry: Economic and Statistical Aspect - Salikhova, O. B. (Statistics of Ukraine, 2023)
Among the priorities for the Ukrainian government during the country’s recovery period after the war should be ensuring national security, establishing an effective healthcare system, creating jobs, achieving stability and economic growth. The development of the pharmaceutical industry plays a crucial role in achieving these goals. The pharmaceutical industry, as revealed by the study, despite increasing production and value added over the years of independence, remains vulnerable and dependent on external resources. The Covid-19 pandemic and the russian military aggression exposed the industry’s unpreparedness for new challenges and threats, casting doubt on the effectiveness of Ukraine’s policy for national pharmaceutical production. The aim of this article is to show initiatives and political decisions made since the early 2000s, as well as economic and statistical assessments of their consequences for the pharmaceutical industry in Ukraine. Study found, that the government’s policy in the process of European integration primarily focused on harmonizing legislative and regulatory frameworks for pharmaceutical activities, rather than on enhancing the domestic manufacturers through a variety of activities: the implementation of a deliberate policy for the technological product and process innovation based on domestic R&D, strengthening competitive advantages for to meet growing domestic needs and increase exports. Lack of policy for increasing the innovative and scientific and technological potential of pharmaceutical industry has led to the growth of imports. It is proven that in 1996, the import of pharmaceutical products per capita in the country was 4,98 and at the end of 2021 (before the start of the war), it was 71.78. The research revealed that Ukrainian pharmaceutical industry, primarily manufactures products for the domestic market and relies largely on imported intermediate goods (as there is no domestic production of fine chemicals, active pharmaceutical ingredients and their intermediates); the industry does not generate foreign currency earnings even to cover the expenses for purchasing necessary ingredients in foreign markets. The article substantiates the necessity of a multi-aspect policy. The formulation of such policies should be based on both the results of statistical analysis from official statistics and surveys of professional associations’ members associated with the pharmaceutical industry (developers and manufacturers of biological and chemical substances, pharmaceuticals, and medical devices, as well as providers of fillers and packaging materials and equipment for pharmaceutical production). This approach will allow for a comprehensive and adequate assessment of the current state and future prospects of the industry.